The Health Consequence of Rising Housing Prices in China - Yuanwei Xu; Feicheng Wang (ZBW - Leibniz Information Centre for Economics, 2020)
China has experienced a rapid boom in real estate prices in the last few decades, leading to a substantial increase in living costs and heavy financial burdens on households. Using an instrumental variable approach, this paper exploits spatial and temporal variation in housing price appreciation linked to individual-level health data in China from 2000 to 2011. We find robust evidence that increases in housing prices significantly raise the probability of residents having chronic diseases. This negative health impact is more pronounced among individuals from low-income families, households that purchased rather than inherited or was allocated the home, and those who migrated from rural to urban areas. We also find evidence that marriage market competition exacerbates these negative health effects, particularly for males and parents with young adult sons. Further empirical results suggest that housing price appreciation induces negative health consequences through increased work intensity, higher mental stress, and reduced sleep time. This paper provides a novel explanation to the increased prevalence of chronic diseases in China.
Keywords: R20; R21; R31; I12; I14; I15; I31; G51; 330; Housing Prices; Chronic Diseases; Health; Marriage Competition; China